Essentials of Exercise and Sport Psychology An Open Access Textbook - Zenko, Zachary; Jones, Leighton (Open textbook library., 2021)
This text represents the collaboration of more than 70 authors from multiple countries. Essentials of Exercise and Sport Psychology: An Open Access Textbook brings this diverse set of experts together to provide a free, open, accessible textbook for students studying exercise and sport psychology. Primarily directed at undergraduate students, this well-referenced book is also appropriate for graduate students.The topics covered are broad, ranging from an Introduction to Exercise Psychology (Chapter 1), to an Introduction to Sport Psychology (Chapter 19), to Working in Sport, Exercise, and Performance Psychology (Chapter 33). Importantly, students should recognize that each author brings their individual perspectives, experiences, and expertise to this book. Therefore, some chapters may share overlapping content, but the content is discussed in unique ways. For example, Chapters 2, 3, 4, and 5 focus on physical activity and exercise behavior. While content in these chapters is related, it is not redundant. To fully understand the complex world of exercise and sport psychology, students are encouraged to engage with diverse perspectives from many authors.Chapters also contain learning exercises to prompt students and instructors to engage with the material on a deeper level. For effective review, students and instructors are encouraged to complete these learning exercises and discuss responses together.The majority of this textbook was written during the global COVID-19 pandemic. We are tremendously grateful for all of the efforts and expertise of the many contributors to this project. Despite the challenges of teaching, researching, and surviving in the pandemic, the authors persisted. As a result, Essentials of Exercise and Sport Psychology: An Open Access Textbook is completed; we think you will enjoy using it as you pursue this challenging and fascinating area of study!